Impact of laser surface texturing (LST) on the tribological characteristics of piston rings and cylinder liners – a review. Part 1: development of LST technology. (3rd September 2021) - Bathe, R. N.; Padmanabham, G.; Thirumalini, S.; Vaira Vignesh, R.
ABSTRACT: Mechanical losses consume about 40% of the total energy developed by a typical automotive engine. The piston–cylinder system accounts for 50% of the engine frictional losses, of which 70% to 80% is attributed to the piston rings. Inadequate lubrication in the parts of the engine reduces the reliability of engines, since high wear, seizure, or catastrophic failure of the components may occur. Moreover, frictional losses adversely affect the economic use of fuel. Therefore, a marginal reduction in frictional losses enables economic fuel consumption and is a significant achievement. Of the various factors, the surface topography of the piston rings and cylinder liner dominates the lubricant flow between them and influences its tribological behaviour. Surface texturing, lubricant formulation, and lubricant additives have undergone significant technological advancements in recent times to satisfy the global requirements of reduced emission and improved fuel economy. One of the emerging technologies for significant improvement in the tribological properties of mechanical components is laser surface texturing. The precise control of the shape and size of the textures (dimples or grooves) and rapid processing rate makes laser surface texturing advantageous. This article reviews the theoretical and numerical methodologies developed to analyse the impact of surface texturing on the friction behaviour of piston ring–cylinder liner contact. In addition, the article presents future directions for the research work on improving the tribological performance of internal combustion engines. The present Part 1 of the article discusses the laser surface texturing process, and Part 2 reviews its use in piston ring–cylinder contact.